The Influence of Good Corporate Governance and Sustainable Finance on the Performance of Commercial Banks - Ivana Winoto; Samuel Tarigan (Green Publisher Indonesia, 2025)
Corporate governance and sustainability are key concerns for companies in Indonesia, particularly those operating in the banking sector, which have implemented corporate governance reforms to enhance the protection of shareholders’ and stakeholders’ interests. In addition, sustainability is required by regulators in the Indonesian banking sector, where its management is often a public consideration in assessing financial institutions, especially banks, as secure places to store their funds. The purpose of this study is to determine whether the implementation of good corporate governance and sustainable finance affects financial performance in banking. The independent variables used in this study are the size of the board of directors, the proportion of independent commissioners, CAR, Big 4 external auditors, and the proportion of credit for sustainable businesses. ROA serves as the dependent variable, while total assets are used as control variables. A purposive sampling method was applied to determine the study sample. Through this method, 47 general banks in Indonesia listed on the Indonesia Stock Exchange (IDX) were obtained. The research data was collected from the 2023 annual reports of all banks. The analytical method employed is multiple linear regression. The results of the study indicate that the CAR and sustainable finance variables have a significant positive relationship with ROA. This finding supports previous research that examined the relationship between CAR and sustainable finance with ROA, confirming that both variables have a significant positive influence. Accordingly, managers may focus on fulfilling these two variables to enhance ROA.